ANALISIS DAYA GENERATOR DENGAN MENGGUNAKAN 4 BUAH SUDU TURBIN TIPE WHIRLPOOL PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) - Wisansono simangunsong (LPPM Politeknik LP3I Medan, 2021)
The depletion of the availability of energy that cannot be produced, such as oil and coal used as fuel for Steam Power Plants (PLTU) and Diesel Power Plants (PLTD) Other alternatives are needed to produce electrical energy and minimize emissions resulting from the combustion process that can be caused by heating global warming, air pollution and the depletion of the ozone layer. For this reason, renewable energy such as Micro Hydro Power Plants (PLTMH) can be needed to meet the electrical energy needs of the community that are environmentally friendly. In this study discusses Generator Power Analysis Using 4 Turbine Blades Type Whirlpool Micro Hydro Power Plant. Data collection in this study was carried out through five tests using the same water discharge of 0.00625 m3/s. So that the final results obtained data in the form of the highest generator power of 11.11 watts, the largest turbine power of 0.570 watts, the highest torque of 0.059 Nm and the best turbine efficiency of 4.05%.